DAEDALUS AND ICARUS: THE PALINGENESIS OF MYTHS IN ZBIGNIEW HERBERT’S POETRY - Hejniak, Zuzanna (Prace Polonistyczne, 2019)
The article provides an overview of scholarly research on the palingenesis of myths in Zbigniew Herbert’s poetry and offers an interpretation of his poem Daedalus and Icarus. The analysis of the text is based on Gilbert Durand’s isotopic classification of images and contextualized in the history of the evolution of the two eponymous mythical characters. This will help examine the changes that Herbert introduced to the classic images of Daedalus and Icarus.